Chemical Characteristics and Acceptability of Bagelen Dry Bread with the Addition of Moringa Leaf Flour (Moringa Oleifera Lam) - Khoerunisa, Puja; Fizriani, Atia; Tubagus, Robi (FoodTech: Jurnal Teknologi Pangan, 2024)
Moringa is a plant that is rich in benefits, because Moringa leaves contain good nutritious food content and can be used as herbal medicine for the body. Moringa leaves can be used to complement nutrition and increase the value of liking in making bread. The purpose of this study was to determine the effect of bagelen bread formulation with the addition of moringa flour on chemical characteristics and acceptability as well as the best treatment for bagelen dry bread. The method used in this study is a completely randomized design (CRD) with 4 levels of treatment and 3 replications. The treatment was done with the addition of moringa flour 0%, 5%, 7%, 10%. Based on the results of the research that has been done, the addition of moringa flour has a significant effect on ash content, protein, fat, carbohydrates, vitamin C, calcium, acceptability of aroma, taste, texture, appearance, and overall attributes but has no significant effect on the water content of bagelen bread. The results of the best analysis of bagelen bread with the addition of moringa flour are in the T1 treatment (95% Wheat flour; 5% Moringa leaf flour) which has the best characteristics including: moisture content 5.51%, ash content 1.95%, protein 9.73%, fat 19.67%, carbohydrates 63.13%, vitamin C 181.18mg/100g, calcium 241.14mg/100g, acceptability testing of aroma attributes 2.44 (like), taste attributes 1.88 (like), texture attributes 2.20 (like), appearance attributes 2.12 (like), and overall attributes 2.04 (like).